Helmutneris vadum, a new species of Lumbrineridae (Annelida) from Lizard Island, Great Barrier Reef, Australia - Borisova, Polina; Budaeva, Nataliya (Zootaxa, 2020)
A new species of Lumbrineridae, Helmutneris vadum n. sp., is described from shallow waters near Lizard Island, Great Barrier Reef, Queensland, Australia. The new species differs from two other known species of Helmutneris by having bidentate maxillae III and no ventral limbate chaetae. Sequences of the fragments of COI and 16S rDNA for two specimens including the holotype are deposited in GenBank. A key for three species of Helmutneris known to date is provided.